DNA methylation abundantly associates with fetal alcohol spectrum disorder and its subphenotypes. (May 2018) - Cobben, Jan Maarten; Krzyzewska, Izabela M; Venema, Andrea; Mul, Adri N; Polstra, Abeltje; Postma, Alex V; Smigiel, Robert; Pesz, Karolina; Niklinski, Jacek; Chomczyk, Monika A; Henneman, Peter; Mannens, Marcel MAM
Aim: Fetal alcohol spectrum disorder (FASD) involves prenatal growth delay, impaired facial and CNS development and causes severe clinical, social-economic burdens. Here, we aim to detect DNA-methylation aberrations associated with FASD and potential FASD diagnostic and prognostic biomarkers.Patients & methods: The FASD diagnosis was established according to golden-standard protocols in a discovery and independent replication cohort. Genome-wide differential methylation association and replication analyses were performed.Results: We identified several loci that were robustly associated with FASD or one of its sub phenotypes. Our findings were evaluated using previously reported genome-wide surveys.Conclusion: We have detected robust FASD associated differentially methylated positions and differentially methylated regions for FASD in general and for FASD subphenotypes, in other words on growth delay, impaired facial and CNS development.